Perspectives on guidance and social inclusion in a global society - Hiebert, Bryan (2005)
The world is changing rapidly. People today face numerous challenges in achieving a meaningful and fulfilling life. In many countries, there are enormous systemic barriers to address, such as: massive unemployment, HIV/AIDS, social disintegration, and inadequate infrastructure. One job for life is over. For many it never existed. Old metaphors and old models of career development no longer apply. New ways of thinking about careers are necessary, that take into account the context in which people are living, the reality of today's labour market, and the fact people's career-life journey contains many branching paths, barriers, and obstacles, but also allies and sources of assistance. Flexibility is important, as is keeping options open and making sure the journey is meaningful. Guidance professionals need to begin early, working with other professionals and those seeking assistance to develop attitudes that facilitate people taking charge of their own career-life paths. People need a vision for their life that will drive a purposeful approach to career-life planning and avoid floundering. Helping people achieve that direction can be most effectively accomplished when policy makers and practitioners work together to ensure that effective and accessible services are available for those who need them and when a large part of focus in on addressing the context in which marginalized people work and live.